Iron Exposure Effects on Seedling Growth of Enterolobium cyclocarpum (Jacq.) Griseb. and Albizia chinenesis (Osbeck) Merr on Water Culture Media - Mohammad Agus Salim; Dede J. Sudrajat; Aditya Nugroho; Fitri Indriani; Evayusvita Rustam; Tri Handayani; Dewi Maharani; Henti Rosdayanti; Hary Wawangningrum; Muhammad Efendi; Janis Damaiyani; Endah Suhaendah; et al. (International Journal of Forestry Research)
Iron (Fe) is a trace element and metal crucial to plant growth and development. However, it can become toxic at high concentrations, potentially harming plants. Information related to the tolerance or sensitivity of forest plants to Fe exposure can be the basis for selecting species to be planted on land with high Fe content. This study aims to determine the growth response and tolerance of Parota (Enterolobium cyclocarpum) and Red sengon (Albizia chinensis) seedlings to Fe exposure. A completely randomized design (CRD) was used in this study, with Fe treatments consisting of nine concentration levels (0, 0.25, 0.5, 1, 1.25, 1.5, 1.75, and 2 mM). Observed parameters included growth metrics (height, root length, dry weight of roots, shoots, and total plants), chlorophyll content, photosynthesis rate, malondialdehyde (MDA) content, and tolerance index. The results showed that Fe exposure significantly affected the growth of E. cyclocarpum and A. chinensis seedlings. For E. cyclocarpum, a Fe concentration of 0.25 mM resulted in the best growth in all growth parameters, whereas, for A. chinensis, Fe exposure reduced all growth parameters. Fe exposure did not significantly impact either species chlorophyll content or photosynthesis rate. The MDA content in E. cyclocarpum seedlings peaked at 1.75 mM Fe, with no significant difference between 1 to 2 mM concentrations. In contrast, for A. chinensis, MDA content increased significantly at 1.25 mM Fe. The tolerance index of E. cyclocarpum seedlings increased significantly at 0.25 mM Fe concentration, but decreased with increasing Fe concentration, while A. chinensis showed a decrease in tolerance index with increasing Fe concentration. This finding suggests that E. cyclocarpum is able to provide greater tolerance to Fe exposure compared to A. chinensis seedlings. E. cyclocarpum can also be recommended as one of the species for rehabilitation and reclamation of marginal lands with high Fe content.